Tax policy cyclicality and financial development - Chrysanthakopoulos, Christos; Tagkalakis, Athanasios (Economics and Business Letters, 2024)
This paper adds to the existing literature by examining the macroeconomic, political and institutional determinants of tax policy cyclicality conditional on financial development. We find that an increase in trade and financial openness leads to pro-cyclical VAT and counter-cyclical CIT rate response in high financially developed economies, while an increase in financial openness is associated with counter-cyclical VAT and PIT responses when the levels of financial development are low. A high public debt ratio leads to a counter-cyclical VAT rate response in economies with low financial development. Political power and fiscal institutions are factors that affect the tax policy cyclicality only in less financially developed economies.